ANTIPLASMODIUM ACTIVITIES OF KELUWIH (Artocarpus camansi) METHANOL LEAF EXTRACTS IN THE MENCIT (Mus musculus) Balb / c INFECTED WITH Plasmodium berghei - Dmitry Arditya Harsya Priangga; Dwi Soelistya Dyah Jekti; Yayuk Andayani (IKIP Mataram, 2013)
Antiplasmodium activity test of methanol extract of leaves of kelwih (Artocarpus camansi) was carried out in vivo in mice (Mus musculus) Balb / c infected with Plasmodium berghei. The purpose of this study was to determine the effective dose of methanol extract of leaves of kelwih as antiplasmodium. Antiplasmodium activity test was carried out in vivo in Balb / c mice that had been infected with Plasmodium berghei. Parameters observed were parasite growth, and parasite inhibition. After the administration of methanol extract of leaves of kelwih and as many as 30 mice were grouped into 5 treatment groups which were given extract doses of 1, 25, 50, 75, and 100 mg / kg BB and one negative control group (without the administration of methanol extract of kelwih leaves). Observations were carried out for 7 days, starting from day 0 (before treatment), 4 days during treatment and 2 days after treatment. The data obtained were analyzed statistically ANOVA using the Kruskal-Wallis H test and continued with Mann-Whitney U test. The results showed that the lowest parasite growth (1.636%) was obtained from the group dose of 100 mg / kg BB, the largest parasite inhibition (72.832% ) also produced by a group dose of 100 mg / kg BB. An extract is said to have positive antimalarial activity if it can reduce parasitemia by 30% or more. A dose of 100 mg / kg body weight produces parasitic growth values, and parasite inhibition is significant to the control (p <0.05). So, from the explanation above, it can be concluded that giving a dose of 100 mg / kg BB of methanol extract of leaves of kelwih has potential activity as an antimalarial.